Playing on common ground: spaces of sport, education and corporate connectivity, contestation and creativity. Issue 1 (2nd January 2020) - Kohe, Geoffery Z.; Collison, Holly
Abstract: In this article we examine connectivities within the 'messy' organizational commons of sport, education and corporate partnerships. As scholars forewarn, there are currently key stakeholders within the commons that that have set agendas, occupied ideological and physical terrain, and legitimized a presence and authority. The intertwining of organizations here is an evident function of an increased symbiosis between sport, education and governmental and non-governmental stakeholders to carve out significant sector spaces, and exert authority and power over the creation, implementation and ownership 'collaborative' and intersectional work. Drawing on spatial theorists, Henri Lefebvre and Yi Fu Tuan, and examples from FIFA and the IOC, we present a conceptual framework of global stakeholder relations. Focusing of processes of thought, production and action, we offer an intersectional critique of the nuances of Sport–Corporate–Education nexus and consider possibilities and potential for sport education spaces to be reconfigured anew.